Variasi Bahasa Berdasarkan Faktor Usia pada Masyarakat di Desa Kertosono Kecamatan Gading KabupatenProbolinggo - Slama Slama; Magfirotul Hamdiah (International Forum of Researchers and Lecturers, 2026)
Language use within a community exhibits diversity influenced by the social characteristics of its speakers; age is one such factor that shapes distinct intergenerational communication patterns. This study aims to describe language variation based on age and the relationship between language variation and age within the community of Kertosono Village, Gading District, Probolinggo Regency. A qualitative descriptive method with an ethnographic design was employed. Data collection involved observation, interviews, and documentation involving community members representing children, adolescents, adults, and the elderly. Data analysis techniques included data reduction, data presentation, and conclusion drawing. The results indicate that language variation among children is characterized by simple, spontaneous language suited to daily communication needs. Adolescents exhibit the use of slang, code-mixing, abbreviations, and social media registers influenced by technological advancements and social circles. Adults employ language that is more structured, polite, and contextual, reflecting their occupations and social responsibilities. Meanwhile, the elderly tend to maintain the use of the Madurese language, traditional vocabulary, and religious terms, influenced by their life experiences, culture, and social values. The relationship between language variation and age demonstrates that age differences influence vocabulary choice, language style, speech structure, and topics of conversation; consequently, each age group possesses distinct linguistic characteristics shaped by social development, life experiences, and communication environments.